Analysis of thermoelectric geometry in a concentrated photovoltaic-thermoelectric under varying weather conditions. (1st July 2020) - Shittu, Samson; Li, Guiqiang; Tang, Xin; Zhao, Xudong; Ma, Xiaoli; Badiei, Ali
Abstract: This study presents a detailed three-dimensional numerical investigation of the optimum thermoelectric geometry in a hybrid concentrated photovoltaic-thermoelectric system under varying weather conditions. Four different thermoelectric leg geometries are considered and their effects on the performance of the hybrid system are studied. The effects of thermoelectric leg height, cross-sectional area and ceramic height on the hybrid system performance are investigated. Furthermore, the effect of convective heat transfer coefficient on the hybrid system performance is studied. The performance of the hybrid system with optimized thermoelectric geometry is compared with that of the hybrid system with original geometry for summer climatic conditions in London, United Kingdom for a duration of 24 h. Results show that thermoelectric geometry optimization can reduce significantly, the negative impacts of the variable weather conditions on the hybrid system performance. Furthermore, results show that the maximum hybrid system power output density with the optimized thermoelectric geometry decreased by 48.29% when the original geometry is used. This study will provide useful insights into thermoelectric geometry optimization in a hybrid system and optimum thermoelectric geometry for performance enhancement. Highlights: Concentrated photovoltaic-thermoelectric with different leg geometries is presented. Optimum thermoelectric geometry in a hybrid system is investigated. Thermoelectric geometry optimization stabilizes hybrid system transient performance. Conventional symmetrical thermoelectric leg geometry is better for hybrid system.